Language use patterns and strategies for children’s English language development : Insights from Chinese descendant mothers in multilingual Malaysia. - Ong, Teresa Wai See (De Gruyter Mouton, 2024)
Through the lens of bilingual first language acquisition, this study exam ines languages used by Chinese descendant children in various domains and home language strategies taken by their mothers to enhance the children’s English lan guage learning. Data were collected by means of an open-ended questionnaire an swered by three Chinese descendant mothers living in Penang, Malaysia. The findings reveal an overarching trend of the children speaking English as their prin cipal language of communication in the domains of home, extended home, and school, thus hampering the acquisition of Chinese dialects as their ethnic languages. Because their mothers see the importance of English in light of today’s competitive educational landscape, they provided reading materials, educational television, and tutoring programmes to improve their children’s English proficiency. The findings suggest that children’s simultaneous dual language acquisition and the resulting use of code-mixing is due to parental home language policies.